Do social interactions in the workplace lead to productivity spillover among co-workers? - Thomas Cornelissen (IZA World of Labor, 2016)
Should one expect a worker's productivity, and thus wage, to depend on the productivity of his/her co-workers in the same workplace, even if the workers carry out completely independent tasks and do not engage in team work? This may well be the case because social interaction among co-workers can lead to productivity spillover through knowledge spillover or peer pressure. The available empirical evidence suggests that, due to such peer effects, co-worker productivity positively affects a worker's own productivity and wage, particularly in lower-skilled occupations.
Keywords: J24; J31; 330; peer effects; productivity; wages; peer pressure; social pressure; knowledge spillover